(untitled) - Sterling, Mary Jane (New Jersey, 2006)
Problem topics can include improper numbers, grouping symbols, using proportions, rationalizing fractions, multiplying and factoring expressions, solving linear and quadratic equations, working with inequalities, and using formulas in story problems.
Keywords: Algebra,Đại số